ANALISIS KINERJA TEKNOLOGI DALAM JARINGAN LOCAL AREA NETWORK UNTUK MELAKUKAN SHARING DATA DENGAN PENDEKATAN GRAPH THEORY DI PT MITRA JALA ARTA - riyan kristian, riyan; Mulyati, Sri (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
This Local Area Network network research is a communication model that allows each node in the network to function as a client and server simultaneously. The LAN network uses graph theory to increase communication efficiency and data distribution. By modeling this LAN network as a graph, where nodes represent peers and edges describe relationships between peers (nodes), we can analyze the structure and dynamics of interactions in the network. This method allows evaluating important metrics such as degree, shortest path, and connection reliability. This method allows identifying interaction patterns and optimizing data distribution flows, which in turn can improve network efficiency and reliability. The analysis results show that the use of graph algorithms can improve LAN network performance in terms of latency and throughput, as well as provide new insights in the development of more efficient LAN protocols. It is hoped that this research will be able to make a significant contribution to the development of decentralized network technology in the future